Et2NH2C6H3(CO2)3SnBr2.4H2O: SYNTHESIS AND INFRARED STUDY - DAOUDA NDOYE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2014)
The title compound has been obtained on allowing [C6H3(CO2)3(Et2NH2)3] to react with SnBr4. The molecular structure of Et2NH2C6H3(CO2)3SnBr2.4H2O has been determined on the basis of the infrared data. The suggested structure is a dimer in which each tin atom is hexacoordinated by two chelating C6H3(CO2)33- anions and two Br atoms. Cy2NH2+cations are involved through hydrogen bonds with non-coordinating CO2 groups. The suggested structure is a cage.